The Influence of Testimonials, Price and Product Quality on Consumer Purchase Interest in Hanasui Products Online - Sari, Nadila Perwita; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : Aims to determine the significant influence between testimonial, price and product quality variables partially and simultaneously regarding consumer interest in purchasing Hanasui products online. Design/Method/Approach : This case uses quantitative methhods collecction techniiques distributting questioonnaires respondents. Data analysis used descriptive statistical testing, This case focuses on multiple linear regression analysis. The sample consists of 40 respondents who have purchased and used Hanasui products online. Research Finding : Testimonial, price not partially significcant effcect on interest in buying Hanasui products. Meanwhile, product quality has a partially significcant efffect on purcchase interest in Hanasui products. Testimonials regarding price and product quallity simultaneously have a significant effect on interest in purchasing Hanasui products. Research limitations : The limitattion case is the difficulty of collecting respondent data.